Poliomyelitis Eradication in Rural Communities: Role of Rotary Clubs in Ogun State, Nigeria: 2003–2019 - Lasisi, Sekinat Adebusola (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The role of international non-governmental organizations (INGOs) in preserving and advancing public health across the world cannot be overemphasized. One of such significant efforts is poliomyelitis eradication programs. As a deadly communicable disease, the global spread of poliomyelitis has attracted pragmatic interventions from several INGOs. The first global initiative to eradicate the disease was the “PolioPlus” program introduced by Rotary International (RI) in 1985. Despite the RI’s pivotal role in the fight against poliomyelitis, little or no research has been conducted towards unravelling the organization’s efforts in Nigeria. This paper investigated the role of Rotary Clubs in eradicating poliomyelitis in rural communities of Ogun State from 1985 to 2019 using historical research design. The study found that notwithstanding the challenges, Rotary Clubs have played significant role in eradicating poliomyelitis from Ogun State through continuous advocacy and sensitization campaigns, mobilization, polio surveillance, funding, and partnership. It concludes that there is the need for this organization to consolidate on the successes recorded thus far in order to achieve a total eradication of poliomyelitis in the world.